Who has the greatest influence on adolescent gaming disorder: parents, teachers, or peers? An interpersonal relationships network model of gaming disorder - Tan, Xinjie; Liu, Chunlin; Yang, WanJun; Hui, Xiao; Zhang, Ling; Chen, Shuanghong; He, Ying (Frontiers in Psychiatry, 2024)
Introduction Gaming disorder (GD) in adolescents is associated with impaired interpersonal relationships, including those with parents, teachers and peers. However, the interpersonal relationships most strongly associated with GD-related maladaptive behaviors are not well established. This study aimed to investigate the associations between these three types of relationships and the manifestation of GD in adolescents. Methods In this cross-sectional study, 1920 Chinese adolescents participated in a survey that assessed interpersonal relationships (parent−child, teacher−student, and peer relationships) and demographic variables (e.g., gender, grade, duration of gaming), and 1414 participants were ultimately included. A network analysis approach was utilized to evaluate the key network metrics of edge weight and node centrality. Results The findings revealed that peer fear and inferiority (r = 0.12) and teacher−student conflict were most strongly correlated with GD, followed by parent−child conflict (r = 0.09). Peer fear and inferiority exhibited the highest strength centrality (0.84), followed by teacher−student conflict (0.83) and parent−child conflict (0.35). Moreover, the duration of gaming was significantly and positively correlated with GD (r = 0.19). Conclusions The present study underscores the significant role of conflict and rejection within interpersonal relationships, particularly among peers, in the manifestation of GD-related behaviors in Chinese adolescents.